Exogenous determinants of entrepreneurial intuition and the mediatory role of psychological capital among potential youth entrepreneurs - Omonigho Simon Umukoro; David Efevogho Okurame (Journal of Global Entrepreneurship Research, 2017)
Some scholars have argued that intuition should be given more importance in scholarly research but not many researchers have investigated intuition in entrepreneurial settings. This study therefore investigated the influence of career adaptability, ambiguity tolerance, achievement need and mentoring support on entrepreneurial intuition and the mediatory role of psychological capital. The quantitative study employed an ex-post facto research design via cross-sectional survey among 1626 youth corps members across selected National Youth Service Corps (NYSC) orientation camps in Nigeria. Simple random sampling via a proportionate stratification technique was used to select youth corps members to participate in the study sample. Results showed that after controlling for the mediator (psychological capital), there was a decrease in the significant predictive value of career adaptability (Ø = .142; p < .05) and mentoring support (Ø = .063; p < .05) on entrepreneurial intuition; indicating partial mediation. However, the significant predictive value of need for achievement (Ø = .006; p > .05) on entrepreneurial intuition was nullified; indicating full mediation. In a bid to enhance the intuitive capacity of potential entrepreneurs, it was recommended that intensive and comprehensive entrepreneurship training (which would include modules of career adaptability, need for achievement and mentoring support) should be incorporated in all categories of tertiary institutions.
Keywords: 650